Supply chain challenges in the Covid-19 pandemic world - Lopes, João M. (2022)
The constraints imposed by the pandemic COVID-19 had profound consequences on companies' supply chain, downstream and upstream. This study aims to evaluate the impact of a disruptive situation such as the pandemic in companies' supply chain, identifying the main constraints and suggesting solutions. To this end, a quantitative multiple case study methodology was used, and interviews were conducted with Portuguese companies. The results show that the companies that most suffered disruption in their supply chain were the most vulnerable and least resilient. With redundancies and strategic risk management, a more flexible supply chain can ensure that its supply chains are not threatened in case of disruptive events. This study has contributed to the literature on Complex Adaptive System theory and the consequences of the pandemic on supply chains. It is original because it is about analysing case studies of Portuguese companies.